Proses Perkembangan Islam pada Masa Awal di Nusantara: Teori Masuknya dan Pusat Pendidikan Islam Masa Awal di Asia Tenggara: The Islam Development Process in the Early Period of the Archipelago: Theory of Entry and the Center for Early Islamic Education in Southeast Asia - Jamaluddin H; Bahaking Rama; Andi Achruh (FAI UIM, 2023)
This study aims to: (1) find out the theory of the arrival of Islam in the archipelago, (2) to find out the development of Islam in the archipelago, and (3) early centers of Islamic education in Southeast Asia. This study uses a qualitative approach with data collection through literature review methods. The results of the study show that for the first time the arrival of Islam in the archipelago was based on several theories, including the Gujarati theory, Mecca theory, Persian theory, Chinese theory, and Egyptian theory. The development of Islam in the archipelago was influenced by trading activities, marriage processes, da'wah activities, and through education. Islamic education centers in the archipelago are carried out in Muslim places of worship (mosques). As for the Islamic kingdoms in the archipelago, namely the kingdom of Perlak, the kingdom of Samudra Pasai, and the Kingdom of Aceh Darussalam.